2014
DOI: 10.1097/pcc.0b013e31829f5efa
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Umbilical Venous Catheter Tip Position With Radiograph

Abstract: For radiograph and ultrasound scans performed within an hour of each other, the cardiac silhouette method more accurately predicts umbilical venous catheter tip than vertebral body level and methods described in previous studies. Catheters are frequently malpositioned. The length of the target zone for optimal umbilical venous catheter tip position is short. Ultrasound assessment of umbilical venous catheter tip position is quick.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 15 publications
2
50
0
8
Order By: Relevance
“…In only 1/40 infants we could not visualize the UVC tip by US. To improve the detection of migration and malposition of UVCs, US is a valuable and feasible tool, as it mostly takes only a few minutes and avoids additional exposure to radiation [17, 24]. Our study showed that inadvertent migration occurs frequently between the placement of the UVC and Day 3.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In only 1/40 infants we could not visualize the UVC tip by US. To improve the detection of migration and malposition of UVCs, US is a valuable and feasible tool, as it mostly takes only a few minutes and avoids additional exposure to radiation [17, 24]. Our study showed that inadvertent migration occurs frequently between the placement of the UVC and Day 3.…”
Section: Discussionmentioning
confidence: 80%
“…Migration of UVCs has been reported anecdotally [15-17]. Case reports described UVC-related complications such as pericardial effusion, left atrial thrombosis, and intrahepatic hematoma in infants with a migrated UVC at the time of detection of the complication [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Umbilikal venöz kateter ucu ideal olarak vena kava inferiorun suprahepatik segmentinde ya da atriokaval bileşke düzeyinde sonlanmalıdır (3,4,6). Direkt radyografide bu düzey inspiryum ya da ekspiryuma göre değişebilmekle birlikte, yaklaşık T8-T10 vertebralar arası olarak bildirilmektedir (2,3,6,10). Ancak preterm bebeklerin vücut ağırlıkları küçük olduğundan, direkt radyografide bir vertebra boyu kadar bir fark dahi UVK malpozisyonuna bağlı komplikasyon gelişimine neden olabilir.…”
Section: Gereç Ve Yöntemlerunclassified
“…Bu düzey direkt radyografide sağ hemidiyafragma düzeyi olarak değerlendirilebilir. Kateter ucunun birçok yayında T8-T10 vertebra düzeyleri arasında olması gerektiği bildirilmiştir (3,6,(8)(9)(10). Kateter fazla ilerletilirse ucu kalpte sonlanırken, az ilerletilirse ucu karaciğer içerisinde kalır ve her iki durumda da çeşitli komplikasyonlara neden olabilir.…”
Section: Introductionunclassified
“…Anteroposterior (AP) and lateral X-rays are commonly used to determine the position of the catheter tip5 6 and to interpret where the cavoatrial junction is 7. When the UVC tip sits too high, the catheter can be withdrawn to a safe position while the operator maintains sterility.…”
Section: Introductionmentioning
confidence: 99%